Colorectal cancer and the rare variant hypothesis - Bodmer, Walter (Henry Stewart Talks, 2007)
Cancer: a somatic evolutionary process, Colorectal cancer: a good model to study, Two clear cut familial forms: FAP and HNPCC, Mutation selection balance for dominants and recessives: application to FAP, APC gene found by positional cloning, Loss of heterozygosity proved its role in sporadic cancers, Selection for mutations in the APC "mutation cluster region", HNPCC mismatch repair genes found by candidate guess, Mutated genes in colorectal cancer include p53 and wnt pathway, occur in adenoma to carcinoma sequence, Arguments for and against need for genomic instability in cancers, Epigenetic changes, Mathematical model of normal and cancerous crypt, Types of familial cancers: mostly rarer than FAP and HNPCC, Approaches to studying multifactorial inherited susceptibility, HLA and disease: the model, Role of linkage disequilibrium, Principles of SNP association analysis, Rare missense variants in the APC gene confer susceptibility, The "rare variant hypothesis" for multifactorial inherited susceptibility: exemplified by study of colorectal adenomas, Update interview: New immune therapy treatments, Update interview: Check point blockers for mismatch repair defective cancers, Update interview: Development of T cell attracting bispecific antibodies targeting CEA(CEACAM5), Update interview: Mutations found in CRC and different spectrum between mismatch repair defective versus non defective CRCs, Update interview: MYH associated polyposis, Update interview: Dominant mutations inPolymerases D and E, Update interview: 40Kb deletion in gremlin leading to Hereditary Mixed Polyposis Syndrome, Update interview: Low effect genetic variants found by Genome Wide Association studies, Update interview: More studies needed on driver gene changes due to methylation, Update interview: Need better understanding of the control of differentiation in CRCs
Updated at 2020/05/15